2011
DOI: 10.1016/j.bandl.2010.09.012
|View full text |Cite
|
Sign up to set email alerts
|

LIFG-based attentional control and the resolution of lexical ambiguities in sentence context

Abstract: a b s t r a c tThe role of attentional control in lexical ambiguity resolution was examined in two patients with damage to the left inferior frontal gyrus (LIFG) and one control patient with non-LIFG damage. Experiment 1 confirmed that the LIFG patients had attentional control deficits compared to normal controls while the non-LIFG patient was relatively unimpaired. Experiment 2 showed that all three patients did as well as normal controls in using biasing sentence context to resolve lexical ambiguities involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 49 publications
4
49
0
Order By: Relevance
“…EV scored 89 on the Peabody Picture Vocabulary Test-IV (Dunn & Dunn, 2007) and greater than Results from normal controls were not available. *Exaggerated interference effects (*p < .05, **p < .01), as reported in Vuong and Martin (2011).…”
Section: Patient Backgroundmentioning
confidence: 76%
See 1 more Smart Citation
“…EV scored 89 on the Peabody Picture Vocabulary Test-IV (Dunn & Dunn, 2007) and greater than Results from normal controls were not available. *Exaggerated interference effects (*p < .05, **p < .01), as reported in Vuong and Martin (2011).…”
Section: Patient Backgroundmentioning
confidence: 76%
“…Our study thus suggests that patients with a deficit in LIFG-based executive control can suffer from a deficit in understanding garden-path sentences as well as syntactically unambiguous ones. Lexical biases prove to be a useful indicator of control demands in sentence processing (see also Vuong & Martin, 2011). Through the manipulation of verb bias, we have observed that a deficit in executive control can result in more severe consequences on sentence processing than previously observed.…”
Section: Discussionmentioning
confidence: 90%
“…Though a range of prior neuroimaging, behavioral, and patient data suggest that common cognitive control procedures help language users resolve conflict during sentence comprehension (Hsu & Novick, 2016; Humphreys & Gennari, 2014; January et al, 2009; Novick et al, 2005, 2009; van de Meerendonk et al, 2013; Vuong & Martin, 2011; Ye & Zhou, 2009), other data suggest distinctions in the cognitive control systems that operate over syntactic and non-syntactic material, leading to claims of domain-specificity (Acheson & Hagoort, 2014; Engelhardt et al, 2016; Fedorenko et al, 2012; Vuong & Martin, 2014). Our study tested the effects of increased conflict resolution demands across four diverse tasks, one of which involved syntactic conflict and three of which did not.…”
Section: Discussionmentioning
confidence: 99%
“…A range of behavioral and neurobiological data support this approach: for example, patients with damage to the LIFG, who show deficits in cognitive control (Hamilton & Martin, 2005; Thompson-Schill et al, 2002), also fail to recover from initial misinterpretations during language comprehension (Novick et al, 2009; Vuong & Martin, 2011). Young children demonstrate similar challenges revising syntactic misanalyses (Huang, Zheng, Meng, & Snedeker, 2013; Trueswell, Sekerina, Hill, & Logrip, 1999; Weighall, 2008), which may be linked to protracted cognitive control development (Mazuka, Jincho, & Oishi, 2009; Novick et al, 2005; Woodard, Pozzan, & Trueswell, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Conflict resolution in language can be syntactic in nature; for example, LIFG-based cognitive control processes have been implicated in resolution of syntactic conflict in garden path sentences (January, Trueswell, & Thompson-Schill, 2009;Novick, Kan, Trueswell, & Thompson-Schill, 2009). Importantly, cognitive control is also recruited to resolve non-syntactic conflicts; for example the LIFG is recruited when resolving conflict between semantic plausibility and thematic roles (Thothathiri, Kim, Trueswell, & Thompson-Schill, 2012;Ye & Zhou, 2008;, resolving competition in lexical selection (Schnur et al, 2009), and resolving semantic ambiguities (Bedny, Hulbert, & Thompson-Schill, 2007;Rodd, Johnsrude, & Davis, 2010;Vuong & Martin, 2011).…”
Section: Cognitive Control As a Shared Resourcementioning
confidence: 99%